The Iron Age looks at Rome for the first time in audiovisuals: fiction, cultural imaginary and historical reality in Barbarians and Britannia - Gago Mariño, Manuel; García Sánchez, Jesús (Ex Novo: Journal of Archaeology, 2021)
Two recent fiction series produced for video-on-demand (VOD) platforms show the conflict between the Roman Empire and indigenous peoples from the perspective of the latter for the first time. Thus, transforming the traditional Roman historical genre into a more diverse and multifocal space. But, in Barbarians and Britannia this new audiovisual optic manages the representation of this historical reality in completely opposite ways.